A new approach for wireless communication systems based on idma technique - Awatif Rouijel; Benayad Nsiri; Ahmed Faqihi; Driss Aboutajdine (2010 5th International Symposium On I/V Communications and Mobile Network, 2010)
—This paper will propose a novel multiple access technology, called OWDM-IDMA (Orthogonal Wavelength-Division Multiplexing-Interleave Division Multiple Access), which is the combination of OWDM (Orthogonal Wavelength-Division Multiplexing) and multiple access schemes IDMA (Interleave Division Multiple Access), in which interleaves are used as the only means for user separation. The IDMA receiver principles for different modulation and OWDM principles are outlined. Simulation example of OWDM-IDMA system is provided to demonstrate the advantages of the OWDM-IDMA scheme in terms of bandwidth by estimating the bit error rate (BER) of system, putting themselves in a real communication.
Keywords: IDMA; OWDM; CWT; DWT; ESE; DWPT; IDWPT